2021
DOI: 10.1016/j.jiac.2020.10.029
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 detection by fluorescence loop-mediated isothermal amplification with and without RNA extraction

Abstract: Rapid and simple point-of-care detection of SARS-CoV-2 is an urgent need to prevent pandemic. Reverse transcription loop-mediated isothermal amplification (RT-fLAMP) can detect SARS-CoV-2 more rapidly than RT-PCR. Saliva is non-invasive specimen suitable for mass-screening, but data comparing utility of nasopharyngeal swab (NPS) and saliva in RT-FLAMP test are lacking and it remains unclear whether SARS-CoV-2 could be detected by direct processing of samples without the need for prior RNA extraction saliva. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…Reverse transcriptase loop-mediated isothermal ampli fication (LAMP) 25 has become the second most common NAAT after RT-qPCR with several advantages over RT-qPCR, including rapid turnaround time within 30 min, ease of implementation, and potential utility at the point of care with a simple device. 11,14,[26][27][28][29][30][31] In 2020 we reported that LAMP had equivalent efficacy to RT-qPCR in detecting SAR-CoV-2 when testing saliva from asymptomatic people in our contact tracing and airport quarantine cohorts. 11 For these reasons, LAMP is currently being used at the international airport quarantine stations in Japan as the confirmatory NAAT test after indeterminate results from CLEIA.…”
Section: Discussionmentioning
confidence: 94%
“…Reverse transcriptase loop-mediated isothermal ampli fication (LAMP) 25 has become the second most common NAAT after RT-qPCR with several advantages over RT-qPCR, including rapid turnaround time within 30 min, ease of implementation, and potential utility at the point of care with a simple device. 11,14,[26][27][28][29][30][31] In 2020 we reported that LAMP had equivalent efficacy to RT-qPCR in detecting SAR-CoV-2 when testing saliva from asymptomatic people in our contact tracing and airport quarantine cohorts. 11 For these reasons, LAMP is currently being used at the international airport quarantine stations in Japan as the confirmatory NAAT test after indeterminate results from CLEIA.…”
Section: Discussionmentioning
confidence: 94%
“…Compared to nasopharyngeal swabs, saliva samples harbor similar levels of viral load while being easier to obtain via self-collection. Several groups have developed RT-LAMP tests to detect SARS-CoV-2 in saliva samples ( Bhadra et al, 2020 ; Flynn et al, 2020 ; Lalli et al, 2020 ; Lamb et al, 2020 ; Nagura-Ikeda et al, 2020 ; Rabe and Cepko, 2020 ; Taki et al, 2021 ; Yokota et al, 2020 ). However, due to pH variability between saliva samples, RT-LAMP often has a high rate of false positives when used with the common pH-dependent dye phenol red ( Bhadra et al, 2020 ; Hardinge and Murray, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the initial months of the pandemic, preprints were released that highlighted alternative strategies apart from RT-qPCR for SARS-CoV-2 detection [10][11][12][13][14][15][16][17] , although robust validation of these techniques using bona fide COVID-19 positive clinical specimens was sometimes lacking. We were able to validate that RT-LAMP could be a specific, reliable, and inexpensive assay, albeit less sensitive, with clinical confirmation by cross comparison with our newly established RT-qPCR pipeline.…”
Section: Discussionmentioning
confidence: 99%
“…The strand displacement and amplification procedure is carried out at a single temperature in less than 30 minutes. Diagnostic tests utilising this technique have been developed for RNA viruses and other pathogens [7][8][9] , and there are now several works focusing on the use of RT-LAMP to detect SARS-CoV-2 [10][11][12][13][14][15][16][17] . We set up a SARS-CoV-2 RT-LAMP assay using the WarmStart Colorimetric LAMP 2X Mastermix commercialised by New England Biolabs (NEB), which allows for visual assessment of DNA amplification.…”
Section: Introductionmentioning
confidence: 99%